2014
DOI: 10.1371/journal.pone.0109878
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence of Metformin-Induced Vitamin B12 Deficiency in Sulfonylurea Combination Compared with Insulin Combination in Patients with Type 2 Diabetes: A Cross-Sectional Study

Abstract: Long-term and high-dose treatment with metformin is known to be associated with vitamin B12 deficiency in patients with type 2 diabetes. We investigated whether the prevalence of B12 deficiency was different in patients treated with different combination of hypoglycemic agents with metformin during the same time period. A total of 394 patients with type 2 diabetes treated with metformin and sulfonylurea (S+M group, n = 299) or metformin and insulin (I+M group, n = 95) were consecutively recruited. The vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
(38 reference statements)
4
32
0
5
Order By: Relevance
“…The mean duration of Diabetes was significantly different among the two groups in the present study implicating that patients requiring Insulin therapy had longer duration of Diabetes than patients on Metformin Monoptherapy. Almost similar findings have been documented by Kang et al 9 , where it has been shown that the patients with Metformin and Sulfonylurea combination had shorter duration of Diabetes than patients with Metformin and Insulin combination therapy. In the present study the average daily dose of Metformin was quite high(1226±450mg).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The mean duration of Diabetes was significantly different among the two groups in the present study implicating that patients requiring Insulin therapy had longer duration of Diabetes than patients on Metformin Monoptherapy. Almost similar findings have been documented by Kang et al 9 , where it has been shown that the patients with Metformin and Sulfonylurea combination had shorter duration of Diabetes than patients with Metformin and Insulin combination therapy. In the present study the average daily dose of Metformin was quite high(1226±450mg).…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been echoed in the cross-sectional studies conducted separately by Kang D et al 9 and Sato et al 14 . The mean duration of Diabetes was significantly different among the two groups in the present study implicating that patients requiring Insulin therapy had longer duration of Diabetes than patients on Metformin Monoptherapy.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations